Pathologic Diagnosis of Achondrogenesis Type 2 in a Fragmented Fetus: Case Report and Evidence-Based Differential Diagnostic Approach in the Early Midtrimester. (January 2014) - Weisman, Paul S.; Kashireddy, Papreddy V.; Ernst, Linda M.
As a group, lethal genetic skeletal disorders (GSDs) usually result in death within the perinatal period. Because lethal GSDs are often ultrasonographically detectible by early midtrimester, dilation and evacuation (D&E) is the method of choice for elective termination of pregnancy in many institutions. However, because the diagnosis of the lethal GSDs relies heavily upon radiologic examination of fetal remains, reaching an accurate diagnosis in this setting can be challenging. We report an autopsy case of a fetus delivered by D&E at 15 4/7 weeks gestation with radiologic, histologic, and genetic findings compatible with achondrogenesis type 2 and discuss an evidence-based differential diagnostic approach to lethal GSDs terminated by early midtrimester D&E.